The Predictive Role of Teaching Experience in Teachers’ Implementation of Metacognitive Knowledge - Khonamri, Fatemeh; Podpera, Rastislav; Kurilenko, Viktoria; Obloberdiyevna, Djamaldinova Shakhlo (Journal of Education Culture and Society, 2024)
Aim. While there is so much emphasis on teachers' metacognition, little is known about the role of teaching experience in teachers' metacognition and their instructional practices. Therefore, the current study aimed to provide new insight into the extent to which experience in teaching might predict teachers' metacognition or their awareness of each metacognitive component and sub-factor. Furthermore, the use of teachers' metacognition in their instructional practices was explored.Method. A quantitative research method was used to investigate teachers’ metacognition and their teaching experience. For this purpose, 130 teachers participated and completed the Metacognitive Awareness Inventory for Teachers (MAIT) questionnaire. Independent T-test and Enter regression were used to analyse the data.Results. The analysis of the collected data revealed that years of teaching experience could be a predictor of teachers' metacognitive knowledge but not their metacognitive regulation.Conclusion. Teachers can enhance their metacognition from the first years of teaching, and through training and practice, they can strengthen their abilities.